2009
DOI: 10.1002/esp.1862
|View full text |Cite
|
Sign up to set email alerts
|

Paraglacial gullying of sediment‐mantled slopes: a case study of Colletthøgda, Kongsfjorden area, West Spitsbergen (Svalbard)

Abstract: International audienceThis paper evaluates the paraglacial evolution of a sediment-mantled slope in a polar maritime environment. The intensity of paraglacial processes is estimated through quantifi cation of erosion and dating of fi eld sectors with the help of photographic archives. Gully erosion has been estimated using morphometric parameters and by surveys of vegetation cover. The rapid melting of dead-ice cores controls gully formation. This leads to slope form modifi cation: gully profi le gradients are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 54 publications
1
39
0
2
Order By: Relevance
“…The permanent decrease of geomorphic activity once Dryas octopetala cover reaches a value of 35% (Figure A) can be interpreted as density or biomass engineering threshold (Figure ; Balke et al , ). A similar vegetation cover threshold, delimiting active from inactive sediment‐mantled slopes, was also found on Svalbard (Mercier et al , ). Once this threshold is crossed, increasing D. octopetala cover amplifies the decrease of geomorphic activity by permanently inhibiting higher magnitude/frequency processes through its above‐ and below‐ground morphological and biomechanical traits (see earlier; Figure , plot 3).…”
Section: Discussionmentioning
confidence: 99%
“…The permanent decrease of geomorphic activity once Dryas octopetala cover reaches a value of 35% (Figure A) can be interpreted as density or biomass engineering threshold (Figure ; Balke et al , ). A similar vegetation cover threshold, delimiting active from inactive sediment‐mantled slopes, was also found on Svalbard (Mercier et al , ). Once this threshold is crossed, increasing D. octopetala cover amplifies the decrease of geomorphic activity by permanently inhibiting higher magnitude/frequency processes through its above‐ and below‐ground morphological and biomechanical traits (see earlier; Figure , plot 3).…”
Section: Discussionmentioning
confidence: 99%
“…In polar regions characterised by the presence of permafrost, rates of landsystem transformation are often expedited by the disintegration of buried ice (Fitzsimons, 1996;Bennett et al, 2000;Etienne et al, 2008;Oliva and Ruiz-Fernández, 2015). For example, Mercier et al (2009) reported that following deglaciation sediment mantled slopes undergo significant transformation, with the formation of gullies controlled by the ablation of buried ice. Conceptual pathways of landsystem evolution predict that upon complete deglaciation, icecored terrain will result in a 'hummocky' assemblage of landform (Boulton, 1972), although preservation of buried ice is permitted under an extensive sediment mantle.…”
Section: Introductionmentioning
confidence: 99%
“…Some papers have examined para-glacial activity in polar and subpolar regions, mainly in the Arctic (e.g. Ballantyne and Benn, 1994;Mercier and Laffly, 2005;Mercier et al, 2009;Rachlewicz, 2010). However, there is a lack of studies focusing particularly on para-glacial processes in Antarctica.…”
Section: Introductionmentioning
confidence: 99%